Reconstructing the historical background of Paul's rhetoric in the Letter to the Colossians - Copenhaver, Adam (Library of New Testament studies, 2018)
Cover -- Half Title -- Title -- Copyright Page -- Contents -- Acknowledgments -- Abbreviations -- Introduction -- Chapter 1 History of Scholarship -- 1. Gnosticism -- A. Review -- B. Critical Summary -- 2. Pagan Religions -- A. Review -- B. Critical Summary -- 3. Hellenistic Philosophies -- A. Review -- B. Critical Summary -- 4. Judaism -- A. Review -- B. Critical Summary -- 5. Summary -- 6. Alternative Approaches -- 7. Conclusion -- Chapter 2 Epistolary Analysis of Audience in Colossians -- 1. Audience in Ancient Letter-Writing -- A. Private Letters -- B. Private Letters Copied and Sent to a Second Audience -- C. Letters with Multiple Recipients -- D. Letters to a Defined Group -- E. Circular Letters -- F. Private Letters Written in Anticipation of a Public Reading -- G. Letters Written in Anticipation of Collection and Publication -- H. Letter-Essays -- I. Official Letters -- J. Pseudepigraphal Letters -- K. Literary Works with an Epistolary Framework -- L. Summary -- 2. Defining the Audience in Colossians -- A. Colossians 1:1-2 -- B. Colossians 2:1 -- C. Colossians 4:7-17 -- i. Recommendation of Letter-Carriers (Colossians 4:7-9) . -- ii. Greetings from Paul's Associates (Colossians 4:10-14) . -- iii. Paul's Greetings and Instructions (Colossians 4:15-17) . -- iv. Summary of Colossians 4:7-17 . -- D. Summary of Audience in Colossians -- 3. Conclusion -- Chapter 3 Rhetorical Analysis of Colossians and the Rhetorical Situation -- 1. Rhetorical Criticism and the New Testament -- A. Historical Survey of Rhetorical Criticism -- B. Exigence and the Rhetorical Situation -- C. Rhetorical Situation and Historical Reconstruction -- D. Summary -- 2. Rhetorical Analysis of Colossians -- A. Epistolary Greeting (1:1-2) -- B. Exordium (1:3-2:5) -- B.i. Prayers (1:3-23). -- B.i.a. Prayer of Thanksgiving (1:3-8). -- B.i.b. Prayer of Intercession (1:9-20).